Analisis Kewajiban Perpajakan PPh 21, PPh 23 dan PPh Final Pada PT Taiba Consulting Indonesia - Mesra Berlyn Hakim; Temon Bagus Hidayahtullah; Tri Winarsih; Umar Yeni Suyanto (Politeknik Ganesha Medan, 2023)
Various policies related to Pandemi Covid 19 have an impact on the decline in the realization of the 2021 State Expenditure Budget as evidenced in the 2020 APBN Realization Data experienced a decrease in the delivery of realization by 19.6%, annual tax notification for Income Tax in 2021, in particular taxpayers experienced Pandemi Covid uncertainty 19, Shortfall factors have a stake in swelling of the realization of budget financing by 6.1% in economic recovery so that it has an impact on slowing the profitability of business entities caused by the policy of increasing installment discounts to 50% and a decrease in corporate income tax rates by 11%. This study was conducted with the aim of finding out the implementation, payment, deduction and reporting of PPh 21 tax obligations, PPh 23, Final Construction Services PPh. The method used in this study uses qualitative, primary and secondary data sources through documentation, observation and interviews. Data analysis uses data reduction, while it is to validate data using the triangulation technique of source, time and technique. The results of the study concluded: (1) Payment, Cutting, and Reporting of PPh 21 in accordance with Law Number 36 Year 2008 concerning Taxation (2) Payment, Cutting, Reporting PPH 23 Not in accordance with Law Number 36 Year 2008, because of the postponement of vendors in PPh 13 payment (3) Payment, Cutting, and Final Income Tax Reporting in accordance with Tax Law Number 36 of 2008.